Framing the Solid South : The State Constitutional Conventions of Secession, Reconstruction, and Redemption, 1861 - 1902 - Herron, Paul E. (Book collections on Project MUSE., 2017)
"Beginning in the antebellum period and continuing through Secession, Reconstruction, and after, Southern States went through a period of intense constitution writing and rewriting mostly through a series of constitutional conventions. These conventions wrote constitutions that protected slavery, allowed for Secession, then allowed them to rejoin the union, and finally enshrined the rule of a white elite and the suppression of black rights. In this book, Herron tells the story of these repeated efforts to write constitutions, arguing that the result was the solid south, a place different from the rest of the country, dominated by a white elite, with weak states, and no rights for African Americans. He contends the peculiar character of the South continues today and understanding the politics of these constitutional conventions and the documents they produced is key to understanding Southern history and the south today"--